2016
DOI: 10.1242/dev.120576
|View full text |Cite
|
Sign up to set email alerts
|

View from the heart: cardiac fibroblasts in development, scarring and regeneration

Abstract: In the adult, tissue repair after injury is generally compromised by fibrosis, which maintains tissue integrity with scar formation but does not restore normal architecture and function. The process of regeneration is necessary to replace the scar and rebuild normal functioning tissue. Here, we address this problem in the context of heart disease, and discuss the origins and characteristics of cardiac fibroblasts, as well as the crucial role that they play in cardiac development and disease. We discuss the dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 124 publications
(164 reference statements)
5
99
0
Order By: Relevance
“…2F) . This is consistent with previously reported data demonstrating that GATA4 is crucial for heart formation during embryonic development and strongly implicated in congenital heart diseases (Butler et al, 2010; Furtado et al, 2016; Garg et al, 2003), and suggests a cardiac endothelium identity for the CMEC-derived endothelial cells.…”
Section: Resultssupporting
confidence: 93%
“…2F) . This is consistent with previously reported data demonstrating that GATA4 is crucial for heart formation during embryonic development and strongly implicated in congenital heart diseases (Butler et al, 2010; Furtado et al, 2016; Garg et al, 2003), and suggests a cardiac endothelium identity for the CMEC-derived endothelial cells.…”
Section: Resultssupporting
confidence: 93%
“…Whether the proliferative capacity of cCFU-F cells in vitro reflects their selfrenewal and progenitor status in vivo requires investigation, and it remains to be demonstrated whether any PDGFRα + cells in the adult mammalian heart have cardiomyogenic potential that could be augmented in a therapeutic setting. Furthermore, the notion of a 'living scar' and the many roles of cardiac stromal cells and descendant myofibroblasts is well established and targeting different aspects of fibrogenesis is an active area of research (Furtado et al, 2016).…”
Section: Cre−ert2mentioning
confidence: 99%
“…The origin of stromal fibroblasts and myofibroblasts is an important consideration in this Review, because in addition to providing a cardiac scaffold and structural integrity to the heart, stromal cells and myofibroblasts regulate organ development, wound healing, stem cell niches and inflammation (Furtado et al, 2016). An early CRE-based lineage-tracing experiment suggested that a subset of cardiac stromal fibroblasts arise de novo via endothelial-tomesenchymal transition (EndMT) from adult endothelial cells (Zeisberg et al, 2007).…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
“…CFs significantly contribute to multiple aspects of cardiac function and disease [53], particularly via modulation of fibrotic remodeling in the heart following injury [10], [54] and [55]. To examine the consequences of GRK2 loss in CFs for cardiac function, authors used tamoxifen-inducible collagen1α2-CreER(T)/GRK2 fl/fl mice (GRK2 fKO mice).…”
Section: Gβγ-grk2 Signaling Manipulation As a Strategy To Treat Camentioning
confidence: 99%